Application of Improved YOLOv5 Algorithm in UAV Patrol Inspection of Datengxia Water Conservancy Project - GUAN Jixiang; GUAN Shifeng (Renmin Zhujiang)
This paper introduced the application of an improved YOLOv5 algorithm in unmanned aerial vehicle (UAV) patrol inspection of the Datengxia Water Conservancy Project.First,the paper introduced the basic principles and characteristics of the YOLOv5 algorithm and then discussed the improvements to the traditional YOLOv5 algorithm.Subsequently,this paper analyzed the application and advantages of the improved YOLOv5 algorithm in the UAV patrol inspection of the Datengxia Water Conservancy Project,including precision,recall,and mAP.Finally,this paper pointed out the application of the YOLOv5 algorithm in the UAV patrol inspection of the Datengxia Water Conservancy Project and proposed feasible improvement schemes.